Childhood sexual abuse among men who have sex with men in urban north China: a cross-sectional survey. (December 2017) - Pan, Stephen W; Li, Dongliang; Tang, Weiming; Ong, Jason; Tucker, Joseph D; Ruan, Yuhua
Abstract: Background: Childhood sexual abuse is associated with HIV vulnerabilities and psychological distress. Research indicates that childhood sexual abuse is also more common among sexual minorities. However, there is limited research into childhood sexual abuse among sexual minorities in China. We describe the prevalence and correlates of penetrative childhood sexual abuse among men who have sex with men (MSM) in urban north China. Methods: Data were collected from July 4, 2013, to March 23, 2014, by anonymous, self-administered, structured questionnaires at MSM HIV testing clinics in Beijing and Tianjin, China. Participants were also recruited via peer referral, gay websites, and community-based organisations. Penetrative childhood sexual abuse was defined as being forced to have sex with someone before age 16 years. Logistic regression was used to assess measures of association. Study protocols were reviewed and approved by the National Center for AIDS/STD Control and Prevention, Chinese Centers for Disease Control and Prevention, and the Providence Health Care Research Institute, University of British Columbia. Findings: Out of 400 respondents, the prevalence of penetrative childhood sexual abuse was 5% (20/400). Median age at experience of penetrative childhood sexual abuse was 13 years (IQR 5 years). 85% (17/20) of perpetrators were older than the survivor (on average older by 7·5 years [SD 5·34]). Median length of relationship between the perpetrator and survivor was 3 months (IQR 24 months). Penetrative childhood sexual abuse was associated with migrant status (crude odds ratio [cOR] 3·65, 95% CI 1·04–12·55) and living with one's wife (4·09, 1·25–13·41). Pre-teen penetrative childhood sexual abuse was associated with Christian religious affiliation (cOR 7·24, 95% CI 1·40–37·30), particularly Catholic religious affiliation (11·71, 1·08–127·16). No significant associations were detected between penetrative childhood sexual abuse and HIV infection, unprotected sex, depression, or anxiety. Interpretation: We found that prevalence of penetrative childhood sexual abuse among urban Chinese MSM in urban North China was lower than in studies among MSM in North America, but higher than studies among Chinese males overall. These findings could help inform interventions to decrease childhood sexual abuse among sexual minority males in China. Funding: Ministry of Science and Technology of China (2012ZX10004-904), the US Fulbright Program, and the Liu Institute for Global Issues.